CADHERIN COMBINATIONS RECRUIT DENDRITES OF DISTINCT RETINAL NEURONS TO A SHARED INTERNEURONAL SCAFFOLD - Duan, Xin (Neuron, 2018)
Distinct neuronal types connect in complex ways to generate functional neural circuits. The molecular diversity required to specify this connectivity could be supplied by multigene families of synaptic recognition molecules, but most studies to date have assessed just one or a few members at a time. Here, we analyze roles of cadherins (Cdhs) in formation of retinal circuits comprising eight neuronal types that inform the brain about motion in four directions. We show that at least 15 classical Cdhs are expressed by neurons in these circuits and at least 6 (Cdh 6-10 and 18) act individually or in combinations to promote specific connectivity among the cells. They act in part by directing the processes of output neurons and excitatory interneurons to a cellular scaffold formed by inhibitory interneurons. Because cadherins are expressed combinatorially by many central neurons, similar interactions could be involved in patterning circuits throughout the brain.